The model of relationships between pay for individual performance and work engagement. Issue 4 (13th August 2018) - Kulikowski, Konrad
Abstract : Purpose: Research on the relationship between pay for individual performance (PFIP) and work engagement (WE) is limited. The purpose of this paper is to present a model outlining a threefold association between PFIP and WE: a direct association, an indirect association via pay satisfaction and a joint indirect association via pay level and pay satisfaction. Design/methodology/approach: Structural equation modeling and bootstrapping procedures were used to test hypotheses with regard to these associations based on data obtained from two independent studies: the author's own research project, and the European Work Conditions Survey 2015. Findings: In both studies, the author found the hypothesized direct association between PFIP and WE; indirect association between PFIP and WE via pay satisfaction; and a joint indirect association between PFIP and WE via pay level and pay satisfaction. Research limitations/implications: Given its limited cross-sectional design, future longitudinal research in this area is needed to test the model of relations presented in this paper. Practical implications: The association between PFIP and WE is weak, and partially mediated by pay satisfaction; thus, it seems that to promote WE, it is not solely sufficient to introduce PFIP into remuneration systems, but that, in addition, PFIP should be aligned with employee pay expectations. Originality/value: This study contributes to the career development literature by proposing and initially testing a model describing the three ways PFIP may be related to WE, one of the most crucial factors in achieving career success.